Revolutionizing Online Education: Integrating Machine Learning and Data Analysis into LMS - Singh, Parveen; Handa, Meenakshi; Haq, Anwal Ul (International Journal of Computer Sciences and Engineering, 2023)
In 2020, the events that transpired revealed the fragility of society and its vulnerability to abrupt shifts in governing paradigms. The outbreak of COVID-19 pandemic globally altered the manner in which people engage in activities such as communication, work, study, and interaction. This resulted in a significant change in the way society operates, including education. To accommodate the new reality, education embraced the use of technology, specifically information and communication technologies. One such example is the increased reliance on learning management systems as a platform for resource management and educational activities. This proposal seeks to enhance the learning experience by incorporating artificial intelligence and data analysis into learning management systems. The aim is to establish robust educational models in the new normal, where students have access to virtual assistants for guidance during online learning.